STRATEGI GURU DALAM PEMBELAJARAN AL-QUR’AN MELALUI E-LEARNIG DI SDN PADA GUGUS 8 CAKUNG JAKARTA TIMUR - NINGATINI NINGATINI (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2022)
The success of a lesson cannot be separated from the teacher's strategy in providing a lesson. A teacher must be able to provide learning to increase the potential and intelligence of students. Teachers must keep the spirit of providing learning even though it is e-learning, and learning the Qur'an is no exception. The purpose of this study was to determine the teacher's strategy in learning the Qur'an through E-learning at SDN in Cluster 8 Cakung, East Jakarta, to find out the supporting factors and obstacles faced and how to overcome these obstacles. This study uses a descriptive qualitative approach. Data collection techniques through participant observation, in-depth interviews, and documentation. The research subjects are principals and teachers of Islamic religious education. The results of this study indicate that: The teacher's strategy in learning the Qur'an through E-learning is the teacher's steps in learning through whatsapp media or through the zoom meeting application. The supporting factors for learning the Qur'an through E-learning are: a) Availability of facilities such as ownership of a cellphone or laptop and an internet network. b) The ability and willingness of teachers and students to operate it. c) Good cooperation with parents in mentoring and guidance, d) Participation of students in learning Al-Quran both in the Al-Qur'an Education Park (TPA). The obstacle faced by the teacher in learning and the solution applied was that there were some children who did not have a cellphone or laptop and an internet network. The solution applied is to provide direction or advice to students to study with their closest friends who can participate in E-learning learning, and provide time leeway in sending learning outcomes. ABSTRAKKeberhasilan sebuah pembelajaran tidak lepas dari strategi guru dalam memberikan sebuah pembelajaran. Seorang guru harus mampu memberikan pembelajaran untuk meningkatkan potensi dan kecerdasan anak didik. Guru harus tetap semangat memberikan pembelajaran walaupun secara E-learning, dan tidak terkecuali pembelajaran Al-Qur’an. Tujuan penelitian ini adalah untuk mengetahui strategi guru dalam pembelajaran Al-Qur’an melalui E-learning di SDN pada Gugus 8 Cakung Jakarta Timur, mengetahui faktor pendukung dan kendala yang dihadapi serta cara mengatasi kendala tersebut. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Teknik pengumpulan data melalui observasi partisipan, wawancara mendalam, serta dokumentasi. Subyek penelitiannya adalah kepala sekolah dan guru Pendidikan agama Islam.Hasil penelitian ini menunjukkan bahwa: Strategi guru dalam pembelajaran Al-Qur’an melalui E-learning merupakan langkah-langkah guru dalam pembelajaran melalui media whatsapp maupun melalui aplikasi zoom meeting. Faktor pendukung pembelajaran Al-Qur’an melalui E-learning adalah: a) Tersedianya sarana seperti kepemilikan ponsel atau laptop dan jaringan internet. b) Kemampuan dan kemauan guru dan anak didik dalam mengoperasikannya. c) Kerjasama yang baik dengan orangtua dalam pendampingan dan bimbingan, d) Keikutsertaan anak didik dalam pembelajaran Al-Quran baik di Taman Pendidikan Al-Qur’an (TPA). Kendala yang dihadapi guru dalam pembelajaran dan solusi yang diterapkan adalah terdapat beberapa anak yang tidak memiliki ponsel atau laptop dan jaringan internet. Adapun solusi yang diterapkan adalah memberikan arahan atau anjuran pada anak didik untuk belajar bersama teman terdekat yang dapat mengikuti pembelajaran secara E-learning, dan memberikan kelonggaran waktu dalam mengirimkan hasil belajar